Effect of Tithonia diversifolia Mulch on Atta cephalotes (Hymenoptera: Formicidae) Nests. Issue 1 (5th April 2015) - Rodríguez, Jonathan; Montoya-Lerma, James; Calle, Zoraida
Abstract : Recent studies have shown an insecticidal effect of Tithonia diversifolia (Hemsl.) Gray (Asterales: Asteraceae) foliage on workers of Atta cephalotes L. and inhibitory effects of this plant on the growth of the symbiotic fungus Leucoagaricus gongylophorus (A. Müler) Singer. To evaluate the potential of T. diversifolia as a biological control treatment of this important pest, we assessed the effect of green manure (mulch) of this plant on natural nests of A. cephalotes, in Cali, Colombia. Three treatments were randomly assigned to 30 nests: 1) green mulch of T. diversifolia, 2) green mulch of Miconia sp., Ruiz & Pav. and 3) unmulched control. Every 2 wk for 6 mo, the surface of the nests was completely covered with leaves. Physical and chemical parameters of nest soil were assessed before the first and after the last application of the mulch. Ant foraging in T. diversifolia -treated nests decreased by 60% after the initial applications of the mulch, while nest surface area decreased by 40%. When the nests covered with T. diversifolia were opened, it was observed that the superficial fungus chambers had been relocated at a greater depth. In addition, microbial activity and soil pH increased by 84% and 12%, respectively, in nests covered with plant residues. In conclusion, the continued use of T. diversifolia mulch reduces foraging activity and negatively affects the internal conditions of the colonies, thereby inducing the ants to relocate the fungus chambers within the nests.